CONDE, Antónia F. (Coord); MIGUEL, Catarina; DIAS, Cristina B.; CID, Isabel; FERREIRA, Teresa – Lux Anima. Iluminuras na Biblioteca de Évora. Lisboa: Althum com, 2017. - Fernandes, Maria de Lurdes Correia (2018)
.